Alterations of serum vitamin K levels and prothrombin time-international normalized ratio during tooth extractions among patients receiving warfarin. Issue 6 (November 2018) - Hakata, Kembun; Okubo, Maki; Hasegawa, Tomonori; Izumi, Sayaka; Komiyama, Yuske; Uchida, Daisuke; Kawamata, Hitoshi
Abstract: Objective: The British guideline described that antibiotic treatment during tooth extraction kills bacteria in the intestine, which reduces their production of vitamin K and leads to an increased prothrombin time-international normalized ratio (PT-INR). In this study, we attempted to clarify the influence of antibiotics on serum vitamin K levels and alteration of PT-INR in patients receiving warfarin. Methods: We measured PT-INR and serum vitamin K levels (K1 from diet and K2 from intestinal bacteria) among 11 patients receiving warfarin during tooth extractions (on days 0, 1, 3, and 5) at Dokkyo Medical University Hospital, Sano Kosei General Hospital and Kamma Memorial Hospital from 2008 to 2018. All patients received 5 days of oral antibiotic treatment after the tooth extractions. Results: There were no significant changes in PT-INR between days 0 and 5. Serum vitamin K1 levels on day 0 were varied. Most patients had decreased serum vitamin K1 levels on days 1 and 3. Mean serum vitamin K1 levels on day 3 were significantly lower than those on day 0 (p = 0.04) in patients who were admitted to Dokkyo Medical University Hospital. Most patients still had low serum vitamin K1 levels between days 3 and 5. Serum vitamin K2 levels in most patients examined were below the detection limit (0.05 ng/ml) except two patients (0.24 ng/ml, 0.06 ng/ml at day 0). Conclusion: It appears that antibiotic treatment during tooth extractions might not affect PT-INR among patients receiving warfarin through the alteration of serum vitamin K2 production by intestinal bacteria.